Structural features of free N-glycans occurring in plants and functional features of de-N-glycosylation enzymes, ENGase, and PNGase: the presence of unusual plant complex type N-glycans - Maeda, Megumi; Kimura, Yoshinobu (Frontiers in Plant Science, 2014)
Free N-glycans are present at micromolar concentrations in plant cells during their differentiation, growth, and maturation stages. It has been postulated that these free N-glycans (FNGs) are signaling molecules involved in plant development or fruit ripening. However, the hypothetical biochemical and molecular function of FNGs has not been yet established. The structure of free N-glycans found ubiquitously in plant tissues such as hypocotyls, leaves, roots, developing seeds, or fruits can be classified into two types: high-mannose type and plant complex type; the former, in most cases, has only one GlcNAc residue at the reducing end (GN1 type), while the latter has the chitobiosyl unit at the reducing end (GN2 type). These findings suggest that endo-β-N-acetylglucosaminidase (ENGase) must be involved in the production of GN1 type FNGs, whereas only peptide:N-glycanase (PNGase) is involved in the production of GN2 type FNGs. It has been hypothesized that cytosolic PNGase and ENGase in animal cells are involved in the production of high-mannose type FNGs in order to release N-glycans from the misfolded glycoproteins in the protein quality control systems. In the case of plants, it is well known that another type of PNGase, the acidic PNGase, is involved in the production of plant complex type FNGs in an acidic organelle, suggesting the de-N-glycosylation mechanism in plants is different from that in animal cells. To better understand the role of these FNGs in plants, the genes encoding these N-glycan releasing enzymes (ENGase and PNGase) were first identified, and then structure of free N-glycans in ENGase knocked-out plants were analyzed. These transgenic plants provide new insight into the plant-specific de-N-glycosylation mechanism and putative physiological functions of FNGs. In this review, we focus on the structural features of plant FNGs, as well as functional features of cytosolic PNGase/ENGase and plant specific PNGase, and putative functions